Co-operative and saving societies (SACCOS) and poverty reduction in Lango and Kigezi sub-regions of Uganda: A comparative empirical study - Eton, Marus; BC, Basheka; Fabian, Mwosi (African Journal of Business Management, 2020)
The paper examines the contributions of co-operative and saving societies in poverty reduction in Lango and Kigezi sub-region. The study adopted a comparative and cross-sectional survey design where bivariate and multivariate data analyses were used to analyze the data. Specifically, correlation and regression analysis were done to determine the relationship between financial contribution by savings and credit co-operative (SACCOS), saving culture and poverty reduction. The findings established that low-income households had inadequate access to cheap and affordable credit. In the two regions, the available credits offered by SACCOS were not cheap per say and the SACCOS offered credit at 10% per month, which translated into 120% per annum. The study reveals that microcredits create long-term indebtedness among the rural poor, and yet households are not competent in managing their finances. The saving culture in Kigezi sub-region is associated with political motivations and support from politicians. In contrast, in Lango sub-region, saving culture is associated with response to government programs that were aimed at reconstructing northern Uganda after the two decades of insurgency. The provision of more financial services would contribute to poverty reduction and training of households on the utilization of financial credit.